Bibliometric study of state observer research applied to internal combustion engine (2018)
The present study was conducted to evaluate the worldwide scientific production related to observers applied to internal combustion engines by taking information from the Web of Science (WoS) database and taking the papers published between 2001 − 2017. The works found are mostly research articles with a total of 130 articles equivalent to 97.01%, of the 134 articles studied, and it was also noted that the production of this type of work increased in the last 3 years, with the maximum value in 2015 being 22 articles, even in those 3 years, the greatest number of references were also found. The United States is the country with the highest number of publications with 42 followed by People´s Republic of China, France and UK with 41, 11 and 11 respectively. Although the USA is the country with the highest number of publications, China has consolidated its position as the country with the highest number of publications and citations in the last 3 years. However, within the top 10 institutes with the highest number of publications, 4 of them are from the United States, among which Ohio State University stands out as the institute with the highest number of publications with 16 (11.9%). On the other hand, the most commonly used words in the documents were observer (91), control (47), engine (47), based (42) and estimation (41).